VOCATIVE EXPRESSIONS OF INTERPERSONAL MEANING IN NHAT KY DANG THUY TRAM AND THEIR TRANSLATIONAL EQUIVALENTS IN LAST NIGHT I DREAMED OF PEACE - Nguyễn Thọ Phước, Thảo (Trường Đại học Quảng Bình, 2018)
One of the most basic functions of language is to create interpersonal relationships between speakers and addressees through the way in which text is worded. Speech act functions establish whether we are offering or demanding, aiding or attacking, creating solidarity or emphasizing social distance. In these and other ways, we use language to take a stance towards and socially orient ourselves and our text to others. In this paper, the author aims to clarify the vocative expressions denoting interpersonal meaning in Nhat ky Dang Thuy Tram and its English version Last night, I dreamed of peace. The author also compares them to find out the similarities and differences in the way of addressing between English and Vietnamese which is very useful for language teachers and students in understanding the a text, in translating from Vietnamese to English and vice versa more correctly and effectively.